2022
DOI: 10.1210/clinem/dgac462
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Gestational Diabetes and its Predictive Value for Postpartum Glucose Disturbances

Abstract: Context DNA methylation in the diagnosis of gestational diabetes Objective To assess the value of DNA methylation in the diagnosis of gestational diabetes (GDM) and in the prediction of maternal postpartum glucose disturbances. Design Two-stage observational between July 2006 and December 2010. Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…An increasing number of studies suggest that environmental factors are associated with epigenetic marks and that those marks may be important to understand interactions between genetics and environmental factors. A few EWAS of GDM in maternal peripheral blood are published so far, but the data is not sufficient for an MRS for GDM due to heterogeneity in diagnosis criteria used as well as their small sample sizes [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies suggest that environmental factors are associated with epigenetic marks and that those marks may be important to understand interactions between genetics and environmental factors. A few EWAS of GDM in maternal peripheral blood are published so far, but the data is not sufficient for an MRS for GDM due to heterogeneity in diagnosis criteria used as well as their small sample sizes [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with recent studies. Ballesteros et al [ 17 ] identified 3 DMPs within LINC00917 , TRAPPC9, and LEF1 genes in GDM women with abnormal glucose tolerance, and also LINC00917 and TRAPPC9 were associated with abnormal glucose levels after 4 years of postpartum. In another study, carried out in maternal blood before the GDM diagnosis, they found five DMPs in COPS8, PIK3R5, HAAO, CCDC124, and C5orf34 genes with the potential to be clinical biomarkers of GDM development [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study on peripheral blood of GDM vs. non-GDM presented five CpGs within COP9 signalosome Subunit 8 ( COPS8 ), Phosphoinositide-3-Kinase Regulatory ( PIK3R ), 3-Hydroxyanthranilate 3,4- Dioxygenase ( HAAO ), Coiled-Coil Domain Containing 124 ( CCDC124 ) and Chromosome 5 Open Reading Frame 34 ( C5orf34 ) with biomarker potential for early therapeutic intervention [ 16 ]. Also, a recent study in peripheral blood identified three CpGs in Long Intergenic Non-Protein Coding RNA 917 ( LINC00917 ), Trafficking Protein Particle Complex Subunit 9 ( TRAPPC9 ) and Lymphoid Enhancer Binding Factor 1 ( LEF1 ) genes, respectively, that may be implicated in the development of GDM and postpartum abnormal glucose tolerance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the ability of differentially methylated CpG sites to aid in the prediction of women who will progress to abnormal glucose tolerance in the post-partum period was reported [ 109 ]. An eWAS was performed in a discovery cohort of 24 women with GDM and 24 controls using DNA from blood collected between 26 and 30 weeks of gestation.…”
Section: Gdm and Epigeneticsmentioning
confidence: 99%